Predicting the Consumers' Intention to Adopt Mobile Shopping: An Emerging Market Perspective - Wong, Choy Har; Lee, Har San; Chua, Beng Hui; Chai, Boon Hui; Tan Han, Garry Wei (2012)
Technological advancement in mobile devices and the growth of wireless internet connections have fundamentally altered the way consumers shop. Mobile shopping (m-shopping) provides benefits such as time saving, convenience and improvement of the overall quality of life. With such tremendous benefits, the adoption rate of m-shopping however is still at the infancy stage. To explore further on this, the study analyses the factors that influence the consumers’ intention to adopt m-shopping which have been sparsely explored by extending the traditional technology acceptance model (TAM) with three additional constructs, namely perceived risk (PR), subjective norms (SN) and personal innovativeness in information technology (PIIT). Using online survey method, 142 usable questionnaires were obtained and subsequently analyzed using multiple regression analysis. The results found that the intention to adopt m-shopping is only determined by PU, PEOU and SN. PR and PIIT, however, require further investigation as they were found to be insignificant with the intention to adopt m-shopping. The study includes not only the implications for researchers but also suggestions on mobile marketing plans for practitioners.